Aquaculture Intrusion Detection System based on IoT Mesh network - Ro, Cheulwoo; Kim, Taehee (IJRDO -Journal of Computer Science Engineering, 2016)
Aquaculture industry has been suffering significant losses from intruders and fishing boats. Toeradicate such intrusions, we suggest a solution for intrusion detection based on Bluetooth meshcommunication. Bluetooth Smart mesh modules incorporated with human motion detect sensors such as PIRon buoys could form an active net for detection of humans and objects. Automatically, Solar power cangenerate sufficient power for each modules. One mesh module which has 3G communication as a mothermodule will communicate with monitoring system. This paper illustrates a proposed solution for aquacultureintrusion detection that claims novel efficiency by employing Bluetooth Smart mesh networks and an IoTplatform.